CD94 expression and natural killer cell activity after acute exercise - Roberts, C.; Pyne, D. B.; Horn, P. L. (Journal of Science and Medicine in Sport, 2004)
This study examined the effects of acute exercise on natural killer (NK) cell numbers, their expression of CD94 and cytotoxic capacity in triathletes over a 10-week training period. Nine highly trained male triathletes (age 25.9+/-4.1 yrs, VO2max 5.14+/-0.33 L.min(-1)) attended the laboratory on weeks 0, 2, 5 and 10 for incremental submaximal and maximal cycle ergometry. Peripheral blood was analysed for white blood cell counts, lymphocyte phenotype and cytolytic activity (51Cr release from K562 cells). Maximum oxygen consumption increased from week 2 (5.14+/-0.33 L.min(-1)) to week 10 (5.28+/-0.32 L.min(-1)). Resting NK cell numbers and their expression of CD94 were not altered over the 10-week study period. Natural killer cells expressing CD94+ were not differentially recruited into the circulation and cytolytic activity of exercise-recruited NKs did not differ from those present at rest. There was longitudinal stability (over the 10 weeks of the study) in CD94 expression on NK cells, exercise recruitment of CD94+ NK cells and cytolytic capacity of NK cells. The distribution and functional activity of NK cells are not markedly influenced by 10 weeks of training in competitive triathletes. Natural killer cytotoxic activity after exercise reflects numbers of NK cells and not a changed activation state of these cells per se.